WHAT FACTORS CAN AFFECT INDONESIAN PROPERTY PRICE? - Pratami, Febtin; Marwa, Taufiq; Andaiyani, Sri; Abukosim, Abukosim (TRIKONOMIKA, 2024)
This study analyses the factors that influence property prices in Indonesia using secondary data from 2008QIII to 2021QII and the Ordinary Least Square (OLS) analysis technique. The study re-sults show that inflation and lending rates have a negative and significant effect on property prices. Economic growth has a positive but insignificant effect, while exchange rates and Loan to Value (LTV) have a positive and significant effect on property prices. The findings suggest that LTV can be used as a tool to control credit growth. An increase in LTV ratio accelerates property credit growth, while a decrease in LTV ratio can slow down credit growth. The recommendation of this study is for the monetary authority to ensure the right time to implement LTV policy in Indonesia.